Synthesis, Characterization and Antifungal Studies of Some As(III), Sb(III) and Bi(III) Complexes with o-Tolyl Ammonium Dithiocarbamate - SHARMA, R.N.; KUMAR, ANIL; ALPANA KUMARI, (MS); SINGH, H.R.; KUMAR, RAKESH (Asian Journal of Chemistry, 2010)
ML2XY, ML2XY2 and M2LX5Y2 stoichiometry containing As(IlI), Sb(IlI) and Bi(lll) complexes with o-tolyl ammonium dithiocarbamate has been prepared and characterised using various physico-chemical techniques such as microanalytical, magnetic measurement conductometric studies, infrared spectroscopy, UV and visible spectral data and 1H NMR studies. The ligand and its metal complexes are screened for their antifungal activities against two fungi (A. niger and C. albicans) and some metal complexes exhibited promising results. However, the presence of a chloride atom attached with the metal system is probably responsible for the increasing activity of complexes.